Reflexões sobre a educação do corpo obeso no contexto midiático : uma análise do programa "Além do peso" da Rede Record de Televisão - Ferreira, Lorena Nascimento (2015)
This study aimed to analyze and discuss the speeches about the obese body publicized by the media. More specifically, our attention turns to analysis of the first season of Reality Show "Além do Peso" which is under siege on the "Programa da Tarde" in the Record Television and Network. The research characterized is by an observational study of descriptive and analytical character of a qualitative nature (MINAYO, 2010). To form the corpus of analysis we direct our focus to the first season of the reality “Além do Peso”. This television program was developed between September 23 and December 20 of the year 2013 and aimed to lead a group of 11 obese people to lose weight, through nutritional education and physical activity, to remain in the race to the final award. From the transcripts of speeches, observation of images and contexts of filming, we perform the analysis of the material from the content analysis of Laurence Bardin (1977). From this, we point first, the education of the obese body as the main argument to make homogeneous discourse that emphasizes the need to regain it to the parameters of contemporary society. We found that, the reconfiguration of body image, physical exercise and healthy eating are used with keys strategies in physiological improvement in obtaining health and a new identity based on body image. Finally, we established a joint suffering with a modern insensitivity speech exalting the body culture as a form of personal success, mitigating issues linked to the pleasures that provide welfare and health to participants. We demarcate also that the speech presented is based on an image culture of ideal body, establishing the individual as the main responsible for this achievement, since it has the 'tools' provided by the program to achieve such success.